Evaluation of Compressive and Tensile Strength of Self-Curing Concrete by Adding Crushed Bricks as Additive Material - Sana T. Abdulhussain (Journal of Engineering)
Curing is an essential stage in the production of concrete because it controls cement hydration and strength evolution. One of the methods of curing is the internal or self-curing which can be achieved by using materials of specific characteristics inside concrete to provide moisture from within the concrete as opposed to outside of it. This water should not affect the water-cement ratio. Lightweight coarse or fine aggregate or using absorbent polymer particles with an ability to keep water inside the concrete mixture can be used for this purpose. This study presents the use of crushed brick as a curing agent and evaluate its effects on the compressive and tensile strengths of concrete at different ages. Four mixes were used: M0, M10, M20, and M30. All the aggregates in mix M0 are natural gravel, while mixes M10, M20, and M30 contain 10%, 20%, and 30% crushed bricks, respectively, as replacement of coarse aggregate. The tests results showed that using crushed brick as a self-curing agent gave compressive strength up to 87.8% and splitting tensile strength up to 169% compared to water-cured concrete.